ENTERTAINING FORMS OF ART (REFERENCE – TRADITIONAL BOARD GAMES) - Sharma, Anuj; Sonika (International Journal of Research -GRANTHAALAYAH, 2026)
Art is a skill-based disposition whose purpose is often understood in terms of pleasure, comfort, luxury and entertainment. The Indian philosopher Vatsyayana identified sixty-four arts, which indicates the vast scope of the field of art. From this perspective, art and skill can be closely associated with entertainment. From prehistoric times itself, entertainment has been a fundamental human necessity. Early humans, while living in caves, fulfilled their daily lives through various activities such as tool-making, hunting, artistic depiction, and forms of recreation. As social changes gradually took place, urban civilizations began to develop. Excavations of the Indus Valley Civilization have yielded a variety of remains, such as beautifully painted terracotta pottery, small terracotta figurines, miniature carts, chariots and toys. These findings reveal that by the historical period, art had reached a high level of excellence. The brilliance of this artistic achievement is evident from the material remains that have survived to the present. In India, toys have always held an important place and have also possessed religious and cultural significance. They were used in rituals and in the narration of mythological stories. Although the basic forms of toys remained largely unchanged, their refinement and sophistication evolved over time. Since ancient times, various games have been played in India as a means of entertainment. Games have remained a fundamental element of Indian culture and therefore, sporting and gaming activities have had a significant influence on art. Through these games, attempts were made to understand mythological narratives and religious ideas. Numerous references to games are found not only in archaeological records but also in literary texts. For instance, the Indian epic Mahabharata mentions the game of Chaupar, while Hindu religious traditions often depict deities such as Shiva and Parvati engaged in play. Indian board games represent a complex form of cultural expression and exist in diverse types and styles. Traditionally games such as Chaupar, Ashtapada, Chaturanga, Pachisi, Chess, Moksha Patam, Ludo and Card games have been preserved to the best extent possible by artists and museums. This research paper aims to examine the historical background, aesthetic qualities, and cultural associations of traditional board games, while also discussing their continued relevance in the modern era.